1971
DOI: 10.1002/pssa.2210060137
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Ordered CuAu Alloy

Abstract: The mechanism of deformation of the ordered CuAu alloy is investigated using electron microscopy. The alloy deformation is shown to be accomplished by slipping; a larger degree of deformation involves the mechanism of twinning. The interaction between dislocations and the boundaries of 90° ‐disoriented domains has been studied. It is shown that the interaction between the dislocations and the domain boundaries is responsible for the high deformation strengthening of the ordered alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…After the first 120 s of ordering, the hardness increases noticeably in comparison with the initial disordered state: intervariant boundaries are well known to be the main obstacle to dislocations in ordered L1 0 crystals [33,34]. The hardness then decreases somewhat at 540 s and beyond: this corresponds to the observed transition from a microstructure comprising two microtwin systems to the well-known mechanically relaxed polytwin microstructure, in which only one set of parallel microtwins are locally present.…”
Section: Ordering At 400°c Of Alloys X1 and Y1mentioning
confidence: 89%
“…After the first 120 s of ordering, the hardness increases noticeably in comparison with the initial disordered state: intervariant boundaries are well known to be the main obstacle to dislocations in ordered L1 0 crystals [33,34]. The hardness then decreases somewhat at 540 s and beyond: this corresponds to the observed transition from a microstructure comprising two microtwin systems to the well-known mechanically relaxed polytwin microstructure, in which only one set of parallel microtwins are locally present.…”
Section: Ordering At 400°c Of Alloys X1 and Y1mentioning
confidence: 89%
“…4b). The study of the deformation behavior of this structure revealed that strength properties of the CuAu alloy depend on the domain size (or, which is the same, the number of domain boundaries) [7]. For example, the yield stress of the alloy, which is virtually devoid of domain boundaries, is 115 MPa [8].…”
Section: Microstructurementioning
confidence: 98%
“…It is known that intervariant boundaries are the main obstacle to both slip or microtwinning in this alloy class. Several complex mechanisms, documented both by analysis and experiment, exist to explain the transmission of slip or twinning across intervariant boundaries [7,8,23,24,26,28,29,33,46]. Superdislocations, when these are vectors of deformation, must recombine and reorganize to pass intervariant boundaries, a process that can be aided by thermal activation [8,23,24,26,28,29,46].…”
Section: Discussionmentioning
confidence: 99%
“…Several complex mechanisms, documented both by analysis and experiment, exist to explain the transmission of slip or twinning across intervariant boundaries [7,8,23,24,26,28,29,33,46]. Superdislocations, when these are vectors of deformation, must recombine and reorganize to pass intervariant boundaries, a process that can be aided by thermal activation [8,23,24,26,28,29,46]. Ordinary dislocations, known to be important vectors of deformation in these structures, as well as microtwin Shockley partial series, must change Burgers vector to pass across an intervariant boundary, therefore leaving "debris" (or "residual") dislocations there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation